Figurative Language in “Like The Way It Be” Song By Sound of a Mirror - Meryantari, Ni Ketut; Ardiantari, Ida Ayu Putri Gita (International Journal of Linguistics and Discourse Analytics, 2024)
This study is entitled Figurative Language in “Like The Way It Be” song by Sound of A Mirror. This study aimed to analyzed the types of figurative language found in the song lyrics. This study used the theory proposed by Perrine (1997) to conduct this study. Qualitative method was employed in this study. Several steps done were collecting the data, such as downloading the song lyric from the internet, listening the song and read the lyric intensively to find out the figurative, and nothing the type of figurative found. The data found then analyzed and presented descriptively based on the theory. The analysis of the data identified six types of figurative language. The data found involved 1 simile, 2 metaphor, 1 apostrophe, 1 paradox, 1 symbol, 1 hyperbole, 1 irony. These findings are significant because they reveal how the artist employs various figurative devices to convey deeper meanings, emotions, and themes within the lyrics. Figurative language adds layers of interpretation, enriching the listener's experience by encouraging them to think beyond the literal meanings of the words. Additionally, the presence of diverse figurative elements reflects the complexity and creativity of the song's composition, showcasing the songwriter's skill in using language to evoke imagery and provoke thought. This analysis not only enhances our understanding of the song’s artistic depth but also demonstrates the importance of figurative language in music as a form of expression